2018
DOI: 10.1002/anie.201703226
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Solar Cells: From the Atomic Level to Film Quality and Device Performance

Abstract: Organic-inorganic perovskites have made tremendous progress in recent years due to exceptional material properties such as high panchromatic absorption, charge carrier diffusion lengths, and a sharp optical band edge. The combination of high-quality semiconductor performance with low-cost deposition techniques seems to be a match made in heaven, creating great excitement far beyond academic ivory towers. This is particularly true for perovskite solar cells (PSCs) that have shown unprecedented gains in efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
329
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 458 publications
(336 citation statements)
references
References 154 publications
(365 reference statements)
3
329
1
3
Order By: Relevance
“…Further increasing the PDA content ( x > 0.03), the perovskite crystal continues to decrease to ≈100 nm, and the grain boundary is difficult to be identified. As highlighted by Saliba et al, grain size of a few hundred nanometer is large enough to guarantee high‐performance devices, whereas grain size of sub‐100 nm is detrimental to the device performance . In addition, Ke et al recently reported that a 2D D–J perovskite ( n = 4) with grain size of ≈100 nm yields a small J sc of 13.69 mA cm −2 but a decent FF of 81.04%, which is similar to our case.…”
Section: Resultssupporting
confidence: 89%
“…Further increasing the PDA content ( x > 0.03), the perovskite crystal continues to decrease to ≈100 nm, and the grain boundary is difficult to be identified. As highlighted by Saliba et al, grain size of a few hundred nanometer is large enough to guarantee high‐performance devices, whereas grain size of sub‐100 nm is detrimental to the device performance . In addition, Ke et al recently reported that a 2D D–J perovskite ( n = 4) with grain size of ≈100 nm yields a small J sc of 13.69 mA cm −2 but a decent FF of 81.04%, which is similar to our case.…”
Section: Resultssupporting
confidence: 89%
“…Perovskite materials have attracted a great extent of research due to their exponentially increasing use in the field of solar cells . Ion mobility inside the perovskite was attributed as the cause for the large measured, direction switchable, photocurrents in symmetric electrodes of heterojunction perovskite solar cells (PSCs) .…”
Section: Introductionmentioning
confidence: 99%
“…Today, the efficiency of PSCs has grown from 3.8 % in single‐junction solar cells in 2008 to more than 25 %, and the tandem solar cells has even reached 28 % . Up to now, the key issues of PSC have become its stability, performance and large‐scale production . This requires optimization of the film morphology, interface, device structure and the fabrication process .…”
Section: Figurementioning
confidence: 99%